Modification of a hard alloy cermet structure upon pulsed electron-ion-plasma irradiation - Ovcharenko V. E. Vladimir Efimovich; Ivanov Y. F. Yury Fedorovich; Ivanov K. V. Konstantin Veniaminovich; Mokhovikov A. A. Aleksey Aleksandrovich; Hua X. Y.; Zhong L.; Hai Y. B. (2016, 2016)
Title screen